Pengembangan Asesmen Formatif Berbasis Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis: Need Assessment Study - Fahmi, Jam'an; Nahadi, Nahadi; Hernani, Hernani (Chemistry Education Department of Education and Teaching Faculty, 2023)
Curriculum, learning, and assessment are the main keys to educational success. Formative assessment is an interactive strategy to identify what must be learned and how teaching is formulated according to educational needs. The questionnaire results show that chemistry teachers in schools still do not utilize formative assessments to measure the progress of the educational process. This research aims to collect information regarding the need for developing formative assessments for problem-based learning to improve students' critical thinking skills in the sub-material of vapor pressure reduction. A qualitative method was used in this research, involving 40 chemistry teacher participants in the province of North Sumatra, Indonesia. Participants were asked questions regarding their views on the need for assessment development through a questionnaire. Several of them were interviewed semi-structured to gain more in-depth information from the questionnaire answers. Data were analyzed using the Miles and Huberman model which consists of the steps: collection, reduction, display, and conclusion. The research results show that teachers agree that PBL-based formative assessments are needed to measure students' critical thinking skills. They suggest researchers choose Ennis's version of critical thinking indicators because they have good detail and warn researchers to practice Problem-Based Learning syntax correctly. Apart from that, it is hoped that successful learning in the classroom can be achieved through the use of products from the development of this formative assessment, namely test instruments and observation sheets.